Feasibility and acceptability of targeted screening for congenital CMV-related hearing loss. Issue 3 (4th March 2014) - Williams, Eleri J; Kadambari, Seilesh; Berrington, Janet E; Luck, Suzanne; Atkinson, Claire; Walter, Simone; Embleton, Nicholas D; James, Peter; Griffiths, Paul; Davis, Adrian; Sharland, Mike; Clark, Julia E
Abstract : Background: Congenital cytomegalovirus (cCMV) is the most common non-genetic cause of sensorineural hearing loss (SNHL) in children. Ganciclovir has been shown to prevent the continued deterioration in hearing of children with symptomatic cCMV, but some children with cCMV-related SNHL are unidentified in the neonatal treatment period. Neonatal cCMV screening provides an opportunity to identify infants with cCMV-related SNHL who might benefit from early treatment. Objectives: To assess the feasibility (ability to take samples before 3 weeks of age and clinical assessment by 30 days of age) and acceptability (maternal anxiety) of targeted CMV testing of infants who are 'referred' for further audiological testing after routine newborn hearing screening programme (NHSP). Methods: Parents of infants who have 'no clear responses' on routine NHSP before 22 days of life in London and North East England were approached. Salivary and urine samples were tested by CMV PCR. At recruitment and 3 months, the short form Spielberger State-Trait Anxiety Inventory measured maternal anxiety. Results: 411 infants were recruited. 99% (407/411) returned a sample; 98% (404/411) successfully yielded a CMV result, 6 had cCMV, all diagnosed on salivary samples taken <22 days of age (1.5%; 95% CI 0.6% to 3.2%). Only 50% returned urine samples compared with 99% returning salivary samples (p<0.001). Using saliva swabs 98% were successfully screened for CMV within 3 weeks. All positive screening CMV results were known by day 23, and 5/6 infants with cCMV were assessed within 31 days. Anxiety was not increased in mothers of infants screened for cCMV. Conclusions: Targeted salivary screening for cCMV within the NHSP is feasible, acceptable and detects infants with cCMV-related SNHL who could benefit from early treatment.